Angioprotection role in arterial hypertension treatment: focus on olmesartan - D. V. Nebieridze; A. S. Safaryan; T. V. Ivanishina; N. L. Vinnitskaya (Кардиоваскулярная терапия и профилактика, 2012)
The paper discusses the role of organoprotection in arterial hypertension treatment. The results of international studies on effectiveness of olmesartan, a modern angiotensin II receptor antagonist, are presented. The available evidence confirms not only a strong antihypertensive effect of olmesartan, but also its vasoprotective characteristics. Olmesartan reduces vascular inflammation, facilitates the regression of vascular wall hypertrophy, and reduces the volume of atherosclerotic plaque. In Russia, the medication Cardosal® has become available relatively recently. Due to the extensive evidence base confirming its antihypertensive and vasoprotective effects, this medication appears promising for various clinical groups of Russian hypertensives. Not only adequate blood pressure control, but also effective reduction in the risk of cardiovascular complications could be expected.